Social comparison at school: Can GPA and personality mutually influence each other across time?. Issue 3 (12th September 2019) - Negru‐Subtirica, Oana; Pop, Eleonora Ioana; Crocetti, Elisabetta; Meeus, Wim
Abstract: Objective: Being a student is an important social role youth play during adolescence and how they approach this role has critical implications for their future development. This three‐wave longitudinal study investigated the links between academic achievement (i.e., GPA) and personality traits, through the lens of social comparison mechanisms. Method: Patterns of effects between students' GPA and personality traits were analyzed at group (i.e., comparing rank‐order differences at group‐level; group effects) and individual (i.e., scores are compared to a student's own mean; within‐person effects) levels. A total of 1, 151 adolescents ( M age = 16.45 years; 58.7% female) participated in the study. Results: Most effects we depicted were from GPA to personality traits. At the group‐level, higher GPA fostered students' Extraversion, Agreeableness, and Openness, while Openness reinforced high levels of GPA. At the individual level, GPA was a protective factor against negative affect, as it drove longitudinal decreases in Neuroticism. Conclusions: GPA had a stronger role in personality formation when it reflected students' standing in the school compared to their peers (i.e., group effects) and to a lesser extent when it reflected changes at personal level (i.e., within‐person effects).